Gender inequality and educational aspirations of women from ethnic communities: the case of tajik women from the Turkestan region - Э. Отар; А. Несипбаева; Х. Беширли (Хабаршы. Психология және социология сериясы)
Gender inequality in education and professional development remains a pressing issue in modern society, especially among ethnic communities. This study analyzes the educational and career opportunities of Tajik women in the Turkestan region of Kazakhstan. The aim of the study is to examine the influence of traditional, Soviet and Western discourses on gender roles, educational aspirations and professional opportunities of Tajik women.